Political Communication Strategies In The Digital Era For Generation Z Voters - Hana Alifatunnisa; Maullidha Azzhahra; Farida Nurfalah (PT Publikasiku Academic Solution, 2024)
The development of the digital era has changed political communication strategies, especially in reaching Generation Z voters. Social media such as Instagram, Facebook and TikTok have become the main platforms for delivering political messages. The purpose of this study is to analyze Generation Z's views on political communication strategies carried out by politicians in the digital era, as well as identify the effectiveness of social media platforms in attracting the attention of young voters. This research uses a qualitative method with data collection techniques through observation and interviews with six informants from Generation Z who have the right to vote. The analysis was conducted by categorizing the data into relevant themes. The results showed that political communication strategies using social media succeeded in attracting Generation Z's attention. Interesting political messaging and visual content are effective in increasing young voters' interest. The informants revealed that casual and familiar language, as well as the use of humor in political content, greatly influenced their engagement. Social media not only facilitates access to political information, but also enables direct interaction between politicians and voters. However, challenges such as the spread of fake news and the need for critical skills in assessing information are significant barriers for Generation Z. Political communication strategies that utilize social media are very effective for attracting Generation Z. However, efforts need to be made to ensure the accuracy of information and build critical skills in assessing news, so that Generation Z can participate informally in the political process.